2003
DOI: 10.1007/s00586-003-0581-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized multi-center study for the treatment of lumbar spinal stenosis with the X STOP interspinous implant: 1-year results

Abstract: Patients suffering from neurogenic intermittent claudication secondary to lumbar spinal stenosis have historically been limited to a choice between a decompressive laminectomy with or without fusion or a regimen of non-operative therapies. The X STOP Interspinous Process Distraction System (St. Francis Medical Technologies, Concord, Calif.), a new interspinous implant for patients whose symptoms are exacerbated in extension and relieved in flexion, has been available in Europe since June 2002. This study repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
205
1
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(223 citation statements)
references
References 58 publications
6
205
1
11
Order By: Relevance
“…The authors concluded that the X-Stop Ò offers a significant improvement in The Zurich Claudication Questionnaire over non-operative treatment after 1-year and 2-year follow-up [13,21] and in improving quality of life [20]. Furthermore, the authors stated that, at 1-year and 2-year follow-up, results were similar to published reports on decompressive laminectomy, with considerably lower morbidity [13,21].…”
Section: Case Studiessupporting
confidence: 67%
See 2 more Smart Citations
“…The authors concluded that the X-Stop Ò offers a significant improvement in The Zurich Claudication Questionnaire over non-operative treatment after 1-year and 2-year follow-up [13,21] and in improving quality of life [20]. Furthermore, the authors stated that, at 1-year and 2-year follow-up, results were similar to published reports on decompressive laminectomy, with considerably lower morbidity [13,21].…”
Section: Case Studiessupporting
confidence: 67%
“…Prior to its PMA, only five studies on the X-Stop Ò were published. These included a prospective randomized multi-center study (191 patients) [13], a study on preliminary experiences in ten patients only [14] and three in vitro studies [15][16][17]. Up to now a total of ten RCTs [13,[18][19][20][21][22][23][24][25] and three cost-effectiveness studies [26][27][28] were published.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the research group was planning to perform a randomized controlled trial (RCT), such a prospective comparative study of this implant is not available in Pubmed. After the introduction of this implant by Senegas, the development of other IPDs followed, such as Minns, X-stop and Coflex [13][14][15][16]. Cadaveric studies did not show any biomechanical difference between the various IPDs, and they were therefore considered as interchangeable, although differences in clinical effectiveness were not investigated [15].…”
Section: Interspinous Process Devices Versus Microdecompressionmentioning
confidence: 99%
“…We have a strong evidence-based specialty. This has been helped by the randomised controlled studies in the new techniques of spinal arthroplasty, vertebroplasty, interspinous spacers and re-evaluation of conventional techniques with the Sciatica study from Holland and the controversial and expensive SPORT studies form North America [1][2][3][4][5]. Not all of these have provided the results we were expecting, particularly the Vertebroplasty studies Buchbinder and Kallmes [6,7].…”
mentioning
confidence: 99%